Pelatihan Pemrograman AutoCAD untuk SMK PGRI 4 Surabaya - Pranowo Sidi; Imam Sutrisno; Gaguk Suhardjito; Ari Wibawa Budi Santosa (Bulletin of Community Engagement, 2025)
AutoCAD is a vital computer-aided design (CAD) tool widely used in civil engineering, architecture, and manufacturing. Mastery of AutoCAD programming significantly enhances the industrial competitiveness of vocational high school (SMK) graduates. This study aims to implement AutoCAD programming training for students at SMK PGRI 4 Surabaya to improve their technical competence and efficiency in using AutoCAD. Employing a project-based learning model, the research evaluated student outcomes through pre- and post-tests. The results indicate a 45% improvement in students’ technical proficiency, particularly in automating repetitive tasks and developing structured design templates using AutoLISP and VBA. The training also enhanced students' ability to create complex technical models and improved their overall design efficiency and problem-solving skills. In addition to technical gains, the training fostered the development of essential soft skills, including teamwork, communication, and creativity, through collaborative, real-world design projects. These findings highlight the effectiveness of integrating AutoCAD programming into vocational curricula to better align with industry needs. Key contributions of this study include: the application of a structured, project-based training model combining CAD and automation programming; empirical evidence of AutoCAD programming’s impact on student readiness for engineering and manufacturing careers; and the dual emphasis on technical and soft skill development, an area often underrepresented in prior research. The study offers practical recommendations for vocational schools to embed programming into CAD instruction, ensuring graduates possess industry-relevant competencies aligned with Industry 4.0 demands